Jaringan Hotspot dengan Sistem Voucher Pada Asrama Mahasiswa Kabupaten Balangan di Kota Malang - Supriadi, Joko; Dewi Indahsari, Rina (JURNAL SISTEM KOMPUTER ASIA, 2024)
The internet network in the Balangan Regency student dormitory in Malang City still uses the provider's default router, where the network goes directly to the user and there is still no network management. This has an impact on frequent slow connections and some don't even get an internet connection. In this article, we will discuss the application of a hotspot network using a proxy with a voucher system as bandwidth management in a student dormitory in Balangan Regency in Malang City. Starting from designing the internet network to enter the proxy, then connecting to the access point to spread the network so that each user can enjoy the network smoothly with even bandwidth. In testing the hotspot network with a voucher system, the dormitory residents have successfully connected to the internet network and run smoothly on smartphone and computer devices. All dormitory residents can enjoy the internet smoothly.